دور جامعة الراية بسوكابومي في نشر اللغة العربية في إندونيسيا / The Role of Ar-Raayah University in Spreading the Arabic Language in Indonesia - Ainun Suci Qur'ani; Ummi Mufida; Syirojul Huda (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2022)
تعد اللغة العربية من أقدم اللغات السامية، وأكثرها ناطقا، وأوسعها انتشارا في العالم. فأهداف هذا البحث ثلاثة هي: (1) معرفة أشكال البرامج من قبل جامعة الراية التي يتم من خلالها نشر اللغة العربية في إندونيسيا، (٢) معرفة العوامل الداعمة لجامعة الراية في نشر اللغة العربية في إندونيسيا، (٣) معرفة إسهام / أثر البرامج في نشر اللغة العربية في إندونيسيا. قد استخدم هذا البحث المدخل الكيفي ومنهج دراسة الحالة، وجمع البيانات عن طريق المقابلة والملاحظة الميدانية وتحليل الوثائق. استخدمت الباحثتان تحليل البيانات لميلس وهوبرمن. ونتائج هذا البحث هي، أن البرامج التي تدعم جامعة الراية في نشر اللغة العربية وهي برنامج فتح قسم تعليم اللغة العربية، إنشاء مركز اللغة العربية، والمجلات المحكمة، وإقامة الندوة العلمية باللغة العربية، ومشاركة المسابقات. وأن أشكال هذه البرامج لها دور كبير في نشر اللغة العربية في إندونيسيا، حيث إن برامجها وعواملها الدافعية تسهم وتؤثر انتشارها في إندونيسيا. Abstract Arabic is one of the oldest Semitic languages, as well as the most extensively spoken and communicated language in the world. This study examines three objectives: (1) discovering the types of programs given by STIBA Ar-Raayah via the spread of Arabic in Indonesia; (2) identifying the variables that assist STIBA Ar-Raayah in spreading Arabic in Indonesia; and (3) recognizing the role of Ar-Raayah programs in the spread of Arabic in Indonesia. This study utilized a qualitative approach, applied case study methodology, and accumulated data through interviews, field observations, and document analysis. Miles and Huberman's data analysis was performed by researchers. The findings of this study suggest that STIBA Ar-language Raayah's activities, including the establishment of the Arabic Language Markaz (MBA), composing scientific publications, hosting international symposiums in Arabic, and participating in contests, have been successful in spreading Arabic. These projects are critical to the development of Arabic in Indonesia. Keywords: Role; STIBA Ar-Raayah; Arabic.